Estimates of Foreign Assets and Liabilities for Ireland - Galstyan, Vahagn (Statistical and Social Inquiry Society of Ireland, 2019)
This paper calculates foreign assets and liabilities for Ireland that are more reflective of foreign activities of Irish-resident entities. This is accomplished by stripping from the Irish international investment position the intermediation component that arises from the activities of investment funds and special purpose entities and, to some extent, correcting distortions arising from redomiciled PLCs, intellectual property transfers and aircraft leasing. My estimations not only reduce substantially gross external positions, but also shrink the extent of Irish net foreign indebtedness from 280 to 80 per cent of modified gross national income.fÞ@
(read before the Society, 14 March 2019)
Keywords: Ireland; foreign assets; foreign liabilities; international investments; 314.15